Moral Evil and Leibniz’s Form/Matter Defense of Divine Omnipotence - Hernandez, Jill Graper (Sophia, 2010)
The purpose of this paper is to demonstrate that Leibniz’s form/matter defense of omnipotence is paradoxical, but not irretrievably so. Leibniz maintains that God necessarily must concur only in the possibility for evil’s existence in the world (the form of evil), but there are individual instances of moral evil that are not necessary (the matter of evil) with which God need not concur. For Leibniz, that there is moral evil in the world is contingent on God’s will (a dimension of divine omnipotence), with the result that even though it is necessary that God exerts his will, there are particular products of his will that are contingent and unnecessary—including human moral evil. If there are instances of evil which are contingent on God’s will and yet unnecessary, then the problematic conclusion for Leibniz’s view must be that human evil depends upon divine concurrence, not just for its possibility in the world (which is necessary) but for its instance (which is contingent). If the form/matter defense of omnipotence contains a true paradox, then God concurs in the form as well as the matter of evil. To assuage this difficulty for Leibniz, I will argue that he could either give up an Augustinian notion of evil, or rely upon a distinction between *potenta absoluta* and *potenta ordinate*, which was popular among important thinkers in the medieval period.